Fell / 2. - Clement-Davies, David, 1961- (Legend of the Sight, 2007)
In Transylvania during the Middle Ages, Fell, a lone wolf with unusual abilities, learns that his destiny is entwined with that of one human, fifteen-year-old Rasha, whose mysterious origins have villagers believing she is a changeling.